Novel spiral with and without patch EBG structures for EMI reduction - Zainal Abidin, Zuhairiah; Qasem, Musaab Abdulghani; Dahlan, Samsul Haimi; Mohd Jenu, Mohd Zarar (Faculty of Electronic and Computer Engineering (FKEKK), Universiti Teknikal Malaysia Melaka (UTeM), 2017)
Electromagnetic bandgap structures (EBGs) have the ability to provide excellent reduction of electromagnetic interference (EMI). In this work, a 3 by 3 spiral with and without patch electromagnetic bandgap planar was fabricated on low cost FR4 substrate with permittivity of 4.3 and thickness of 1.6mm. Both designs have dimensions of 36 mm x 36 mm covering 9 unit cells planar design. The simulation and experimental characteristics are illustrated in this paper. An acceptable agreement between the simulated and measured results was obtained. It was found that the spiral without patch EBG experienced better bandgap than the spiral with patch design, which covered bandgap of (5.8 – 7.4 GHz) with relative bandwidth of 22.56%. Meanwhile, for the spiral with patch structure, it covered C band (4.5 – 7 GHz) with extended relative bandwidth of 43%. The results of the characteristics demonstrate that the proposed EBGs are attractive candidates for the integration into the high speed circuitry designs where spiral with patch can be involved in C band applications to suppress the EMI emitted by their circuitry.